การวัดระดับความสุขและวิเคราะห์ปัจจัยที่ส่งผลต่อ ความสุขของประชากรในพื้นที่เมืองเก่าน่าน - ปิณฑิรา วีรจิตโต (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The purpose of this study is to study the level of happiness and happiness indicators including to study the factors affecting happiness of the population in Nan Old City. The data was collected via a questionnaire with 616 samples. The Ordered Logit model and Ordered Probit model which the measurement were divided into 5 levels, 6 indicators (economic, social, political and cultura, environment. And health) and 44 components were used to analyze the factors affecting happiness of the population in Nan Old City by estimating a simple modification of the log-likelihood and marginal probability or marginal effect. The results showed that all 6 happiness indicators has affected the happiness level of the population in Nan Old City. By some of the components of all 6 happiness indicators can be described as a variant of the happiness level of the population in Nan Old City statistically significant. Moreover, the estimations of the happiness level showed that there is a moderate level of happiness among the population in Nan Old City. And the cultural indicator is the most important indicator by the respondents and the estimation of the Ordered Logit model is suitable for data analysis to study this happiness level measuring and the analysis off Affecting happiness of the population in Nan Old City